"I DIDN'T EXPECT HIM TO BE BORN EARLY " - MATERNAL EXPERIENCE REGARDING HOSPITALIZATION IN THE NEONATAL INTENSIVE CARE UNIT - Caroline Sissy Tronco; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula; Andressa Peripolli Rodrigues; Marlene Gomes Terra; Juliane Dias Aldrighi (Universidade Federal do Paraná, 2015)
The aim was to understand the experience resulting from pregnancy interrupted by the premature birth of the baby requiring hospitalization in the Neonatal Unit. It is a phenomenological investigation with a Heideggerian framework, undertaken in December 2010 - May 2011, through interviews held with seven mothers whose children were hospitalized in the neonatal unit of a teaching hospital. In relation to the fact of having a pre-term baby who needed to be hospitalized, the women indicated pregnancy-related health problems which led to the premature birth, and want to understand what is happening. Furthermore, they continue to be frightened even when they are accustomed to their child's hospitalization. As a result, it is necessary to make possible a dialogic relationship and a relationship of support for the mothers so that they may develop strategies for re-establishing the bond with the baby and the care for the specific demands posed by prematurity.